Disaster Victim Service Application at the Social Services of Tangerang District - Ade Setiadi; Sulaiman Sulaiman; Fifit Alfiah (Universitas Raharja, 2022)
The social service of Tangerang District is a government institution that caters to the social welfare problem and one of the services that will be discussed is the service of disaster victims in the district of Tangerang that have not been computerised so that the running system is less efficient. The process of service that is still having difficulty due to the collection of disaster victims is still far from the word accurate and to get the service should often visit the office so it takes a lot of wasted time. Since the system is running less efficiently, a Disaster Victim Service Application has been made which is computerized and runs more efficiently. The method used in data collection is observation, interviews, and literature study. In analyzing a system using the PIECES method (Performance), (Information), (Economy), (Control), (Efficiency), (Service) to make it easier to analyze the running system and provide solutions in making application programs and writers in making application design with visual modelling using UML (Unified Modelling Language) to make a diagram, Hypertext Preprocessor (PHP) as a programming language, and MySQL as a database to be used in the system. The results of the design discuss how to create a system that runs and the proposed system and the existence of this system can facilitate service employees in receiving accurate reports so as to shorten the time of handling in serving victims affected by disasters.